2022
DOI: 10.3390/toxics10070359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Arbuscular Mycorrhizal Fungus on the Growth of and Cadmium Uptake in Maize Grown on Polluted Wasteland, Farmland and Slopeland Soils in a Lead-Zinc Mining Area

Abstract: Arbuscular mycorrhizal fungi (AMF) exist widely in soil polluted by heavy metals and have significant effects on plant growth and cadmium (Cd) uptake. Cd contents differ among wasteland, farmland and slopeland soils in a lead-zinc mining area in Yunnan Province, Southwest China. The effects of AMF on maize growth, root morphology, low-molecular-weight organic acid (LMWOA) concentrations and Cd uptake were investigated via a root-bag experiment. The results show that AMF increased maize growth on Cd-polluted so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The strain used in this study was Funneliformis mosseae , which is highly tolerant to Cd and was provided by the Beijing Academy of Agriculture and Forestry’s Institute of Plant Nutrition and Resources (BGCYN05, 1511C0001BGCAM0013) [ 24 ]. Hoagland solution was prepared from modified Hoagland formula, iron salt solution and trace element solution [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The strain used in this study was Funneliformis mosseae , which is highly tolerant to Cd and was provided by the Beijing Academy of Agriculture and Forestry’s Institute of Plant Nutrition and Resources (BGCYN05, 1511C0001BGCAM0013) [ 24 ]. Hoagland solution was prepared from modified Hoagland formula, iron salt solution and trace element solution [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, oxalic acid was reported to be present at concentrations between 0.55 and 1.53 mg g −1 in the potato genotypes also used this study [ 18 ], and it was lower than the concentrations reported in the present study. The presence of AMF in Solanum lycopersicum plants has been shown to increase the contents of LMWOAs such as oxalic, succinic, and citric acids [ 53 ], and in corn plants, an increase in the exudation of these compounds due to inoculation has been reported [ 54 ]. For instance, in a study evaluating the effects of the AMF Rhizophagus aggreatus , Claroideoglomus etunicatum , and Funneliformis mosseae on corn plants, 10 LMWOAs were isolated and identified, but the compositions of the exudates varied depending on the growth stage and the fungal strain used as inoculant [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytoremediation, using plants to remove toxic metals from the soil, is gaining popularity as a feasible and environmentally friendly method of cleaning polluted land [118,253]. According to reports, AMF has developed strategies that involve immobilizing metallic compounds, precipitating particles of phosphate in the ground, adsorbing chitin within the cell wall made up of fungus, and, ultimately, chelating heavy metals inside the AMF [254]. These strategies could reduce heavy metallic dangers in blended subculture systems and, as a result, from the natural pecking orders [255].…”
Section: Bioremediationmentioning
confidence: 99%